Teaching on Chinese Writing in Binus University - Feng, Ma (Bina Nusantara University, 2011)
Combination of practice teaching Chinese as a foreign language in BINUS University, this article takes the Chinese writing teaching as an example, and analyses “as the student core, as the fun concept” writing modes. Firstly, serious explain: increasing the vitality of classroom teaching, using multimedia methods to make students get interested in; Secondly, article practice: making the written expression be the basis and revealing true feelings as commander, constantly pursue the aesthetic article; Thirdly, feedback and communion: using Facebook, Binusmaya, Binusblog, Chinese newspapers and other channels of interaction to communicate between teachers and students. Through the three steps, we could select the theme which students loved, create a relaxed atmosphere in the writing class, and then the students will be pleasure of writing gradually.